Diabetes Prevention for Pacific People in the United States: A Mixed-Methods Feasibility Study to Adapt the Diabetes Prevention Program With Samoan/Tongan Church Communities. Issue 1 (1st January 2022) - Parks, Courtney A.; Panapasa, Sela V.; Yaroch, Amy L.; Fricke, Hollyanne E.; Resnicow, Kenneth
Abstract : Objective: To determine baseline characteristics of a group of Samoans/Tongans in Southern California at risk for type 2 diabetes mellitus and identify barriers, cultural factors, and readiness and capacity to implement a culturally tailored Diabetes Prevention Program (DPP) in a faith-based setting. Design: A mixed-methods pilot that included piloting modified DPP sessions, conducting a survey, and focus groups (N = 4). Setting: Samoan/Tongan faith-based organizations. Participants: Samoan/Tongan church members in Southern California who were interested in lifestyle behavior change. Main Outcome Measures: Surveys assessing sociodemographic, acculturation, health status, food insecurity, and psychosocial factors. Focus groups focusing on attitudes toward the curriculum, opportunities for tailoring, and specific barriers/facilitators for healthy weight, nutrition, and physical activity. Results: Participants (N = 47) were on average 42 years old, female (57%), and identified as Pacific Islander (35% Samoan, 30% American Samoan, and 35% Tongan). Ninety-eight percent of respondents were overweight/obese, and 45% of households were food insecure. Less than half of respondents were born in the United States, and 28% reported "poor" or "fair" English proficiency. Those with higher body mass indexes were more likely to score lower on internal locus of control and self-efficacy for healthy eating and were motivated to lose weight to feel in control of their health. Focus group results revealed that members of the Samoan/Tongan communities are "underserved" and experience a lack of culturally relevant programs to address obesity and chronic disease. Several barriers to healthier lifestyles were identified including adaptation of traditional recipes made in the United States (ie, to be less healthy), role of stress, cultural values (eg, preference for larger body size), and lack of awareness about healthy lifestyles. The church was identified as a resource that could be leveraged further to positively impact health outcomes. Conclusions: Results demonstrate possible ways to tailor the DPP for US-based Samoan/Tongan populations by harnessing cultural traditions and addressing existing barriers and psychosocial constructs.